Local governance, people's participation and development : precon ditions for peace and stability - Nina, Daniel
Discussion paper to professor Apolo Nsibambi's paper facilitators an d inhibitors of decentralization of power in Uganda, 1962-1993.
AR/MISR/95/1/1
English
Shelf no. 1.
Keywords: Decentralization in government